2021
DOI: 10.3390/ani11082456
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Reporting in Preclinical Urethral Tissue Engineering Studies: A Systematic Review to Assess Adherence to the ARRIVE Guidelines

Abstract: Preclinical research within the area of urethral tissue engineering has not yet been successfully translated into an efficient therapeutic option for patients. This gap could be attributed, in part, to inadequate design and reporting of the studies employing laboratory animals. In this study, a systematic review was conducted to investigate the quality of reporting in preclinical studies utilizing tissue engineering approaches for urethral repair. The scope was on studies performed in rabbits, published betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 73 publications
2
12
0
Order By: Relevance
“…Temporal analysis observed that the re ection ratio of the ve factors included in ARRIVE and NIH at the same time increased over 14 years. The nding of the present study is concordant with observations made by Tariq et al [46] that claims that the quality of reporting enhanced marginally over the study period when analyzing the ARRIVE scores of the 28 articles in preclinical urethral tissue engineering from 2014 to 2020 [48]. However, in Table 4, the statistically signi cant re ection rate increased after the NIH guidelines were established, whereas it was not after the ARRIVE guidelines appeared.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Temporal analysis observed that the re ection ratio of the ve factors included in ARRIVE and NIH at the same time increased over 14 years. The nding of the present study is concordant with observations made by Tariq et al [46] that claims that the quality of reporting enhanced marginally over the study period when analyzing the ARRIVE scores of the 28 articles in preclinical urethral tissue engineering from 2014 to 2020 [48]. However, in Table 4, the statistically signi cant re ection rate increased after the NIH guidelines were established, whereas it was not after the ARRIVE guidelines appeared.…”
Section: Discussionsupporting
confidence: 91%
“…The study design elements may have been performed but not reported, which could result in an underestimation of their presence. However, previous studies were also conducted by assuming that the methodological study designs applied in the experimental process would have been mentioned in the article [45,48,56,73] and underreporting of performance of methodological rigour is rare [19,51]. Therefore, it is believed that it has not had a signi cant impact on our results.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Still, it's highly important to show how bad the portrait is today. The ARRIVE guidelines were first launched in 2010 [3] but they didn't stick as they should and poor reporting performance of preclinical studies has persisted in several fields [4][5][6]. Among the worst reported items is euthanasia and, as pointed out by you, only 14% of the articles fully described the procedure.…”
Section: Dear Dr Nunamaker and Dr Reynoldsmentioning
confidence: 99%